Chemoselective reductive alkynylation of tertiary amides by Ir and Cu(i) bis-metal sequential catalysis. Issue 80 (19th September 2016) - Huang, Pei-Qiang; Ou, Wei; Han, Feng
Abstract : We report a versatile method for the direct, catalytic reductive alkynylation of tertiary amides to give propargylic amines. Abstract : We report herein a convenient and versatile method for the direct reductive alkynylation of tertiary amides to give propargylic amines through sequential Ir-catalysed hydrosilylation–Cu(i )-catalysed alkynylation. The reactions proceed chemoselectively at the amide group in the presence of several sensitive functional groups including the very reactive aldehyde group on either the amide or the alkyne coupling partner. The method is general for tert -amides with or without α-hydrogen.